Discourse, Power, and Resistance Down Under
VIII, 204 p.
Keywords: DPR Down Under Volume 2 draws together a spirited collection of papers presented at the Australian Discourse Power and Resistance conference held in Darwin 2012. The volume of work addresses and seeks to contextualise the problematic question “What counts as ‘good’ research and who decides?” Each chapter in this volume, written from differing theoretical and methodological positions articulates a notion of what could be considered as being ‘good’ research and is, in some way involved in speaking a truth back to power. The chapters invite the reader to rethink and reconsider the inherently political, critical and subversive nature of research from a range of critical investigations.